2017
DOI: 10.3168/jds.2017-12663
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Genetic parameters for milk protein composition predicted using mid-infrared spectroscopy in the French Montbéliarde, Normande, and Holstein dairy cattle breeds

Abstract: Genetic parameters for the major milk proteins were estimated in the 3 main French dairy cattle breeds (i.e. Montbéliarde, Normande, and Holstein) as part of the PhénoFinlait program. The 6 major milk protein contents as well as the total protein content (PC) were estimated from mid-infrared spectrometry on 133,592 test-day milk samples from 20,434 cows in first lactation. Lactation means, expressed as a percentage of milk (protein contents) or of protein (protein fractions), were analyzed with an animal mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 14 publications
4
31
3
1
Order By: Relevance
“…These associations could explain weaker r g to wavenumbers from the protein-, fat-, and lactose-region (Table 2). Consistent weaker genetic correlations have also been observed for LGB content in milk, when studying genetic correlations between milk contents of LGB, α-lactose, α S1 -CN, α S2 -CN, β-CN, and κ-CN (Sanchez et al, 2017). Within the fat-regions, wavenumbers in fat-i were associated with fat A (Kaylegian et al, 2009), transfat (Hewavitharana and van Brakel, 1997), and DGAT1 (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 61%
“…These associations could explain weaker r g to wavenumbers from the protein-, fat-, and lactose-region (Table 2). Consistent weaker genetic correlations have also been observed for LGB content in milk, when studying genetic correlations between milk contents of LGB, α-lactose, α S1 -CN, α S2 -CN, β-CN, and κ-CN (Sanchez et al, 2017). Within the fat-regions, wavenumbers in fat-i were associated with fat A (Kaylegian et al, 2009), transfat (Hewavitharana and van Brakel, 1997), and DGAT1 (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 61%
“…Polymorphism and milk quality studies have been widely used in the optimization of dairy population, and the link between milk composition and genetic variation in milk production has a profound impact on dairy production [2,3,24,25]. Recently, Poulsen et al found that α-LA is a major component, which has negative effect on milk coagulation in Danish Jersey [26].…”
Section: Discussionmentioning
confidence: 99%
“…Milk protein components have an important influence on milk production traits [1], and mainly affect by genetic factors [2,3]. There are six major milk protein components (α S1 -CN, α S2 -CN, β-CN, κ-CN, α-LA, and β-LG) in bovine milk [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Cheesemaking properties (CMP) are strongly related to bovine milk composition (Wedholm et al, 2006). In the PhénoFinlait project, we predicted protein and fatty acid milk composition using mid-infrared (MIR) spectrometry in the French Holstein, Montbéliarde, and Normande dairy cattle breeds (Ferrand-Calmels et al, 2014;Sanchez et al, 2017a). Genome-wide association study (GWAS) on whole-genome sequences imputed using data of run 4 of the 1,000 bull genome project (Daetwyler et al, 2014) led to the identification of candidate causative mutations in 24 candidate genes (Boichard et al, 2014;Sanchez et al, 2017b).…”
Section: Short Communicationmentioning
confidence: 99%
“…Moreover, 15 milk composition traits (Table 1) were predicted from MIR spectra using equations of prediction previously developed in PhénoFinlait (Ferrand et al, 2012;Ferrand-Calmels et al, 2014;Sanchez et al, 2017a) and Optimir (Gengler et al, 2016) projects. These included 6 proteins (α-LA and β-LG whey proteins and α S1 -CN, α S2 -CN, β-CN and κ-CN), 4 fatty acids (total SFA, UFA, MUFA, and PUFA), and 5 min- BeadChips.…”
Section: Short Communicationmentioning
confidence: 99%